Effectiveness of an Educational Package Based on the Theory of Five-Factor Positive Thinking Skills on Psychological Capital Components in Adults - Chamzadeh Ghanavati, Mana; Golparvar, Mohsen; Farhadi, Hadi (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This research aimed to assess the effectiveness of an educational package based on the theory of five-factor positive thinking skills on psychological capital in adults. Methods and Materials: The method was a quasi-experimental design with two groups and three stages: pre-test, post-test, and follow-up. The sample consisted of 40 individuals (20 females and 20 males), selected through purposive sampling and randomly assigned to either the experimental group (20 people, males and females) or the control group (20 people, males and females). The Psychological Capital Questionnaire by Luthans et al. (2007) was used for data collection. The training group received 8 sessions of 100 minutes each, while the control group received no training. Data were analyzed using repeated measures analysis of variance and Bonferroni post hoc test. Findings: Results indicated that in the variable of psychological capital, the components of self-efficacy, hope, optimism, and resilience showed significant differences between the pre-test and the post-test/follow-up stages (p < 0.01), meaning that the training in five-factor positive thinking skills was effective in the post-test phase and this effectiveness was sustained and enhanced up to the follow-up stage. Conclusion: Given the impact of the findings, the use of this training in psychological associations and counseling centers is recommended.